Theresian Flags at the Croatian History Museum and their Iconographic Symbolism (Povijesni prilozi (Historical Contributions), 2019)
Flags from Maria Theresa’s era had regulated guidelines that had to be obeyed in orderto produce the most representative as well as the most typical baroque banners. Theongoing military reforms launched by Maria Theresa, in conjunction with state-governingreorganizations, are also mirrored in the Collection of Flags and Streamers atthe Croatian History Museum. In particular, there are four main representative flagsthat, on the one hand, show the practice of exhibiting statehood statuses by means ofdynastic symbols on battalion standards, and on the other indicate the iconographicsignificance of saints and beatified kings on ceremonial and commemorative banners.These instructions were all done under the impression of the baroque style, the Age ofEnlightenment, and the turbulent time of confl ict in Maria Th eresa’s reign.